A Gill Histopathology Study in two Native Fish Species from the Hydrographic Douro Basin. (12th February 2019) - Santos, Dércia; Luzio, Ana; Coimbra, Ana M.; Varandas, Simone; Fontaínhas-Fernandes, António; Monteiro, Sandra M.
Abstract: Gill histopathology is a valuable tool to evaluate ecosystems health, because the gill is a key site of waterborne pollutant uptake and the first target organ to their toxicity. Consequently, this makes it important in biomonitoring programs. This study aims to evaluate gill histopathological differences in Douro basin native fish species and determine possible associations with water quality and the ecological status classifications. Two native fish species ( Pseudochondrostoma duriense and Luciobarbus bocagei ) were sampled in four points of the Douro basin: two reference points, Ameixiosa (Paiva River) and Covelas (Bestança River), both classified with an excellent ecological status; and two disturbed points, Castro Daire (Paiva River) and Alvações do Corgo (Corgo River), categorized with a good and a moderate ecological status, respectively. Gill histopathological differences were qualitative and quantitatively analyzed. The histological analysis showed that, in all sampling locations, both species presented some degree of gill differences, such as epithelial lifting, lamellar fusion, and/or necrosis. The histopathological differences evaluation emphasized some variances in the responses between the two species. In nase, the filament and lamellar epithelium proliferation were the histopathological differences that better reflected the river ecological status classification, proving their usefulness in biomonitoring programs.